Medição da evaporação em tanques classe a instalados em ambientes aquático e terrestre - Pinto, Fabrício Alves (2009)
The main objective of this research was to compare evaporation measured in two Class A evaporation pans. The first one installed 15 cm over the surface and the second one installed at surface level in a small reservoir. The experiment was carried out at the Fisheries Station of the Federal University of Ceará, in Fortaleza. An automated weather station was installed at the same site. During February to November of 2008, evaporation data were measured in a daily basis. The weather data were collected in a weekly basis using a radio frequency system. The evaporation measured at a soil surface was 5.3% higher than the evaporation measured at a water surface level of the reservoir. The different installation conditions were influenced differently by the weather parameters. The evaporation estimation methods of Penman, Linsley and Linacre underestimated the evaporation measured in the reservoir, and the Penman method presented the smaller error